Uma investigação colaborativa sobre mudança curricular nos cursos profissionais das escolas secundárias públicas - Orvalho, Luísa (2013)
Curriculum innovation refers to the process of curriculum design and to its development. This communication presents a part of a PhD research: a qualitative research case study based on a 1 methodological approach to collaborative action research (C-A-R), carried out in two public secondary schools during the academic years 2008/09 and 2009/2010, involving the coordinators and teachers of vocational courses (VC). For the analysis of change we used as a frame of reference the Model of Curriculum Innovation proposed by Alonso (2006), appropriately adjusted for vocational education and training (VET). We intend to discuss our results in these areas: - how the modular structure (MS) is being understood by teachers and developed in public secondary schools (PSS); - constraints and critical success factors identified in its implementation; - proposals for improvement to develop practices consistent with the recommended theoretical model and successfully implemented in vocational schools. We believe that this research makes a significant contribution in this area of knowledge - vocational education and training. Although the results cannot be generalized, they still open a wider window to observe and understand how MS is being implemented in the PSS, and thus be able to build new proposals for improvement.